2012
DOI: 10.1021/jf302355e
|View full text |Cite
|
Sign up to set email alerts
|

Identificaton of 2,3-Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one Isolated from Lactobacillus pentosus Strain S-PT84 Culture Supernatants as a Compound That Stimulates Autonomic Nerve Activities in Rats

Abstract: Intestinal administration of various lactobacilli has been reported to affect autonomic neurotransmission, blood pressure, and body weight in rats. In this study, three molecules (peaks A, B, and C) were isolated from Lactobacillus pentosus strain S-PT84 (S-PT 84) culture supernatants. Intraduodenal (ID) injection of these molecules increased or inhibited renal sympathetic nerve activity (RSNA) in rats as follows: peak A, 134%; peak B, 40.1%; peak C, 408%. Furthermore, we identified peak C as 2,3-dihydro-3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…It is possible that some compounds are of microbial origin. For example, b-cyclocitral is a cyanobacterial metabolite (Zhang et al, 2013) and 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one is an antioxidant produced by some Lactobacillus bacteria (Beppu et al, 2012;Hwang et al, 2013). However, both these compounds are also present in insectpollinated Eucomis species (Shuttleworth & Johnson, 2009, which suggests that they have a floral origin.…”
Section: Importance Of Floral Scentmentioning
confidence: 99%
“…It is possible that some compounds are of microbial origin. For example, b-cyclocitral is a cyanobacterial metabolite (Zhang et al, 2013) and 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one is an antioxidant produced by some Lactobacillus bacteria (Beppu et al, 2012;Hwang et al, 2013). However, both these compounds are also present in insectpollinated Eucomis species (Shuttleworth & Johnson, 2009, which suggests that they have a floral origin.…”
Section: Importance Of Floral Scentmentioning
confidence: 99%
“…In our previous study, the phytochemical profile of FHD using high-performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS) analysis identified 2,3-dihydro-3,5-dihydroxy-6-methyl-4­( H )-pyran-4-one, 5-hydroxymethyl-2-furancarboxaldehyde, and quercetin . 2,3-Dihydro-3,5-dihydroxy-6-methyl-4­( H )-pyran-4-one was shown to increase the BAT sympathetic nerve activity and the body temperature above the interscapular brown adipose tissue in rats . Quercetin is also well known to display a thermogenesis-mediated antiobesity effect. , In a study by Kaşıkcı et al, quercetin showed oral bioavailability of about 24%, which was slightly lower compared to 52% of isoquercetin, another component of FHD.…”
Section: Discussionmentioning
confidence: 99%
“…DDMP DDMP was identified as a major component with strong DPPH radical scavenging activity in the aqueous extract of BDM-X [29]. It is also isolated from several resources other than fungi, such as lactobacterium [43] and onion [44], and reported to have several physiological functions, such as being anti-inflammatory, anti-mutagenic and having cancer cell toxicity and affecting autonomic neurons. Tyrosinase inhibitory activity reported for DDMP is interesting because BDM-X has potential for cosmetic use [45].…”
Section: Selective Isolation and Quantification Of Major Ingredientsmentioning
confidence: 99%